Clinical and functional effects of radiosynoviorthesis in haemophilic patients with chronic synovitis. A prospective study. Evidence Level: IV - Faraco, F.; Uribe, A.; Toro, A.; López, J.; Faraco, M.; Gómez Barrera, M. (Revista Colombiana de Ortopedia y Traumatología, 2016)
Background: The joint haemarthrosis is the most common manifestation in patients with haemophilia, whereas radioisotope synoviorthesis (radiosynoviorthesis) is a widely used procedure for the treatment of chronic synovitis in order to prevent progression to a chronic arthropathy. There are no available reports of the clinical or functional outcomes of patients undergoing radiosynoviorthesis. The aim of this study was to describe the sociodemographic characteristics and clinical and functional response of patients with chronic haemophilic synovitis in which radiosynoviorthesis was performed. Methods: Between January 2010 and December 2012 in a high complexity centre, all patients with chronic haemophilic synovitis that received radiosynoviorthesis as a treatment were included in a prospective cohort. The joint function Gilbert scale for haemophilia patients was applied to each patient, identifying sociodemographic, clinical and functional features prior to the procedure. A minimum follow-up of one year after the intervention was achieved for each patient, when the Gilbert scale was applied once again to determine the functional outcome of the involved joint. Results: The mean functional Gilbert scale score was 7.95 before the procedure, and 5.53 after the procedure representing statistical significance (P=.002). The improvement mainly depends on three characteristics: the frequency and haemarthrosis characteristics, the presence of joint effusion, and pain. Other variables measured by the scale of Gilbert Scale remained almost constant after the procedure. Discussion: We found an improvement in the scale of Gilbert after the procedure, with significant difference mainly pain control (P=.005) and episodes of hemarthrosis. An improvement in the number and characteristics of haemarthrosis was observed in 84% (P=.001) of patients. These results are encouraging for the use of radiosynoviorthesis as a very good alternative for the treatment of haemophilic patients with chronic synovitis. Evidence Level: IV.